Prosody of the directive speech acts: from commands to pleas - Velásquez, Eva; Velásquez, Eduardo (Lenguas Modernas, 2018)
Prosody plays an important role in the pragmatic differentiation of statements. However, it is an aspect that has hardly been explored despite recent research in the field. In this article, we are presented with the prosodic features that allow the differentiation between commands and pleas in reading and directed speech data. The data is collected using a list of statements and a role questionnaire. The prosodic analysis is within the frame of the Autosegmental Metric (AM) model. The Spanish Tones and Break Indices (Sp-ToBI) is used as a labeling system and the Praat program is used as a tool for the analysis. The results allow us to clearly recognizethe prosody of the commands and pleas both in statements composed of a single word and more complex statements. In both cases, the prosodic component aims to identify the commands based on a L+¡H* nuclear tone with an L% falling tone at the end, along with a reduction in syllable duration and a broader range in the tonal field. Pleas, on the one side, present the pattern H* LM% or M% in conjunction, a lengthening in the last syllables of the statement and a reduction in the tonal field.